Understanding religious and spiritual aspects of human service practice - Ellor, James W (Social problems and social issues (Columbia, S.C.), 1999)
This guide offers advice on direct practice concerns, including spiritual assessment, positive and pathological uses of religious practice, and the need for spiritual self-awareness among human service workers.